Riset Living Qur???an Mengenai Ritual Pembacaan Yasin 41 Di Pondok Pesantren Musthafawiyah Purbabaru - Linda Lisnawati; Bambang Husni Nugroho; Zaki Mubarak (Program Studi Ilmu Al-Qur'an dan Tafsir, 2021)
This research describes in detail the process and meaning of the tradition of reading Surah Yasin 41 for teachers and students at the Purbabaru Musthafawiyah Islamic Boarding School which was held when they were facing a critical situation or had both personal and congregational needs. Using data obtained from documentation, direct observation and interviews, this research analyzes with a phenomenological approach related to the living Qur'an. This research found that the tradition of reading Yasin 41 in Mustafawiyah has a reference base from a Syafi'iyah cleric named Sheikh Ahmad Ad-Dairobi. yasin is accompanied by moving the gundal and patting the right thigh with one clap) and the closing stage (prayer reading). And according to the teachers and students who practice it, this ritual means the hope of salvation and a prayer so that the wishes will be immediately granted.